2017
DOI: 10.3847/1538-4365/aa582f
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-static Modeling from Sunrise/IMaX: Application to an Active Region Observed with Sunrise II

Abstract: Magneto-static models may overcome some of the issues facing force-free magnetic field extrapolations. So far they have seen limited use and have faced problems when applied to quiet-Sun data. Here we present a first application to an active region. We use solar vector magnetic field measurements gathered by the IMaX polarimeter during the flight of the Sunrise balloon-borne solar observatory in June 2013 as boundary condition for a magneto-static model of the higher solar atmosphere above an active region. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…In test II, the MHS extrapolation takes about 6.5 CPU hours on a 2.1GHz processor. An application to IMaX vector magnetogram embedded by HMI data (about 2000 × 2000 grids, see Wiegelmann et al (2017)) needs large amount of computational resources. For practical application, we can limit calculation to the Sunrise-FOV (936 × 936) to reduce the computation.…”
Section: Influence Of Noisementioning
confidence: 99%
“…In test II, the MHS extrapolation takes about 6.5 CPU hours on a 2.1GHz processor. An application to IMaX vector magnetogram embedded by HMI data (about 2000 × 2000 grids, see Wiegelmann et al (2017)) needs large amount of computational resources. For practical application, we can limit calculation to the Sunrise-FOV (936 × 936) to reduce the computation.…”
Section: Influence Of Noisementioning
confidence: 99%
“…Rather, they play a role in heating their local surroundings, if they release their energy at these layers. Jafarzadeh et al (2017a) showed with the help of the magnetostatic solution of Wiegelmann et al (2017) that the shorter SCFs map fields that are more vertical. A number of the transverse waves we have identified are found along these short fibrils.…”
Section: The Structures Listed Inmentioning
confidence: 99%
“…These extrapolations are based on magnetohydrostatic equilibria and have been described by Wiegelmann et al (2017). They also employ wider FOV but lower resolution and lower sensitivity SDO/HMI data (Pesnell et al 2012;Schou et al 2012).…”
Section: Observations From Sunrise 31 Observations and Reductionmentioning
confidence: 99%
“…Deviations from force-free fields occur mainly below 2 Mm in the mixed plasma-β upper photosphere and chromosphere. For more detail, see Wiegelmann et al (2017). We limit our displays to the FOV of the SUNRISE/IMaX images and to a height of up to only 1400 km for better visualization.…”
Section: Magnetic Field Extrapolation Using a Magnetostaticmentioning
confidence: 99%